2022
DOI: 10.22161/ijaers.94.7
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the initial benchmark for the sustainability of Arabica coffee-growing householders in a highland region, Brazil

Abstract: The production of specialty coffees is an important activity for farm incomes and should be encouraged. However, it is necessary that this process may respect the principles based on the economic, environmental, and social axes of sustainability. This research was carried out aiming to generate the initial benchmark of the sustainability of four farms in the municipality of Afonso Cláudio, State of Espírito Santo, Brazil. The System for Assessing Sustainability Standards for Coffee Growing in Espírito Santo, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
0
0
10

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 7 publications
3
0
0
10
Order By: Relevance
“…In the evaluation carried out on the farms, it was found that the economic axis presented the lowest scores compared to the other axes, and the coffee growers did not obtain maximum scores (100 points) in more than five indicators. These data corroborate the results obtained by Viçosi et al (2022) which highlights the need for planning and control in farm management. Winter et al (2020) noted the need for attention in relation to the adequacy of this axis; in a study carried out with small Ethiopian coffee growers, the authors found that they were also not organized in terms of optimizing profits.…”
Section: Economic Axissupporting
confidence: 90%
See 2 more Smart Citations
“…In the evaluation carried out on the farms, it was found that the economic axis presented the lowest scores compared to the other axes, and the coffee growers did not obtain maximum scores (100 points) in more than five indicators. These data corroborate the results obtained by Viçosi et al (2022) which highlights the need for planning and control in farm management. Winter et al (2020) noted the need for attention in relation to the adequacy of this axis; in a study carried out with small Ethiopian coffee growers, the authors found that they were also not organized in terms of optimizing profits.…”
Section: Economic Axissupporting
confidence: 90%
“…The social axis showed the highest scores in the evaluation, and all farms obtained scores above the average, ranging between 67 and 83 points, corroborating the results of Viçosi et al (2022). In the three farms evaluated, the main indicators that contributed to these high scores (100 points) were in relation to the absence of children, forced or hazardous labor, freedom of organization of employees, salaries of employees are compatible with the market, access to education, access to health services.…”
Section: Social Axissupporting
confidence: 83%
See 1 more Smart Citation
“…Além disso, as condições socioambientais têm ganhado aspecto relevante por grande parte dos países importadores. Daí a importância em buscar métodos alternativos de produção, considerando que a sustentabilidade da cafeicultura de arábica no Espírito Santo tem sido trabalhada nas vertentes econômica, ambiental e social, além de processos de certificações (SOUZA, 2022;VIÇOSI et al, 2022).…”
Section: Introductionunclassified
“…Por tais questões, surge a necessidade de que novas técnicas de manejo fitossanitário e ou de sistema produtivos que venham a ser implantadas na cafeicultura capixaba com o uso dos conceitos das boas práticas de produção agrícola (BPA), da produção orgânica e agroecológica, como se apresentam os Sistemas Agroflorestais (SOUZA, 2015;SOUZA et al, 2020;SOUZA, 2022).…”
Section: Introductionunclassified

Tópicos em Agroecologia, Volume 4

José Passos Rangel,
Candido G. Berilli,
de Fátima M. de Oliveira
et al. 2023